2021
DOI: 10.2147/rmhp.s302309
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Among Medical Students Toward the Clinical Usage of e-Cigarettes: A Cross-Sectional Study in a University Hospital in Saudi Arabia

Abstract: Background: To assess knowledge and attitudes about e-smoking among undergraduate medical students, specifically focused on favorable view of therapeutic e-cigarette use for smoking cessation or harm reduction. Methods: This cross-sectional study included medical students at King Abdulaziz University, Saudi Arabia. A six-item subscale was used to explore knowledge and attitudes about the therapeutic use of e-cigarettes, measuring participants' likelihood of favoring such use. A four-item questionnaire measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…In fact, to date of this publication, e-cigarettes products have not been approved by the FDA as smoking cessation aids [ 22 ]. Those findings are comparable to the results reported at a Saudi university where the majority of medical students didn’t know that e-cigarettes were not approved by the FDA as a smoking cessation aid [ 18 ]. Moreover, a meta-analysis of 26 studies has shown that the probability of adult smokers quitting smoking is lower in smokers who use e-cigarettes for smoking cessation compared to non- e-cigarette users [ 21 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, to date of this publication, e-cigarettes products have not been approved by the FDA as smoking cessation aids [ 22 ]. Those findings are comparable to the results reported at a Saudi university where the majority of medical students didn’t know that e-cigarettes were not approved by the FDA as a smoking cessation aid [ 18 ]. Moreover, a meta-analysis of 26 studies has shown that the probability of adult smokers quitting smoking is lower in smokers who use e-cigarettes for smoking cessation compared to non- e-cigarette users [ 21 ].…”
Section: Discussionsupporting
confidence: 84%
“…Compared to the prevalent results reported in the previously cited studies and taking into consideration that the methods used in those studies may not be similar, the prevalence reported in this study indicates an increase in the e-smoking rate among university students in Jordan which could be an alarming sign of the increase of e-cigarettes smoking popularity among young adults in Jordan. Looking at neighboring countries, a study from Saudi Arabia has shown that the prevalence of e-cigarette smoking was more at 11.5% among medical students [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the health colleges students' attitude toward ECs, 46.2% supported using them as a smoking cessation product without any scientific basis. This reiterates the results re-ported by Alzahrani et al, where one-third of medical students agreed on using ECs as a smoking cessation method ( 39 ). Despite that, a study from China reported that only 9.5% EC users had successfully quit smoking ( 14 ).…”
Section: Discussionsupporting
confidence: 83%
“…According to the students' perception toward ECs, 62.8% confirmed that ECs are used as a fashionable alternative of conventional cigarettes, and 59% agreed on ECs being potentially a gateway to smoking for non-smokers and smoking addiction for conventional cigarette smokers, which goes hand in hand with the previous report by Alzahrani et al on medical students where 50.6% agreed that ECs were addictive ( 39 ). Similarly, Almutham and colleagues showed that 49.6% of medical students believed ECs were addictive ( 19 ).…”
Section: Discussionmentioning
confidence: 56%